PENYULUHAN PECEGAHAN POSTPARTUM BLUES MENGGUNAKAN TERAPI EMOTIONAL FREEDOM TECHNIQUE (EFT) - Meita Robbiatul Zukhruf; Itryah Itryah (Jurnal Abdimas Bina Bangsa, 2023)
Postpartum blues is characterized by symptoms such as depression/sadness, crying, rapid mood swings, anxiety, headaches, unsteadiness, self-blame, feelings of inadequacy, difficulty sleeping and poor appetite. This activity uses Emotional Freedom Technique Therapy (EFT) to Prevent Postpartum Blues. Methods of observation and discussion/question and answer. Before starting counseling on how to use Emotional Freedom Technique (EFT) therapy to prevent postpartum blues, it turns out that many pregnant women do not know anything about postpartum blues and how to prevent postpartum blues during menstruation. after birth Meanwhile, after discussing how to prevent postpartum blues during childbirth with the help of emotional freedom therapy for pregnant women, it turned out that many pregnant women received information about postpartum blues and how to prevent postpartum blues during childbirth. Postpartum blues is a period of emotional instability characterized by crying behavior, irritability, anxiety, confusion, and difficulty sleeping. This negatively affects the health of the mother and the development of the child. Postpartum mothers are expected to be able to fulfill their physiological and psychological needs